Watching "Game of Thrones" how audiences engage with dark television - Barker, Martin 1946-; Smith, Clarissa; Attwood, Feona 1964- (Manchester University Press, 2021)
Game of Thrones was an international sensation, and has been looked at from many different angles. But to date there has been little research into its audiences: who they were, how they engaged with and responded to it. This book presents the findings of a major international research project that garnered more than 10,000 responses to an innovative 'qualiquantitative' questionnaire. Among its findings are: a new way of understanding the place and role of favourite characters in audiences' responses; new insights into the role of fantasy in encouraging thinking about our own world; and an account of two combined emotions - relish and anguish - which structure audiences' reactions to controversial elements in the series.
Keywords: Game of thrones; Medienwirkungsforschung; Fernsehen; Game of thrones (Television program) / History and criticism; Television viewers / Attitudes; Television viewers / Psychology; Television series / History and criticism; Television Studies; Television; PERFORMING ARTS; Television; Genres; Drama; Electronic books